Experiences of family vacation with children diagnosed with autism spectrum disorder (ASD) : leisure or work - Fauzunnasirah Fazil,; Habibah Ahmad,; Hamzah Jusoh,; Susheel Joginder Singh,; Er, Ah Choy; Noordeyana Tambi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The goal of the travel and tourism industry is to make all travellers happy. The activities in the sector consistently promote multitudinous benefits, such as wellness, rejoicing, and recuperation. The motivation for family tourists is to indulge in tourism activities that can instil family and social values through a family vacation. However, the vacation experience usually differs for families of children diagnosed with autism spectrum disorder (ASD) compared to regular families of regular children. The development difficulties in the intellectual and social communication of children with ASD involving a spectrum of emotion, namely happy, frustrated, distressed, and restlessness require special attention from their caregivers during vacation. The purpose of this paper was to analyse vacation experiences in families of children with ASD based on the literature of previous studies. The findings indicated that family vacation promotes self-improvement and opens room for learning about the real world in these targeted children. Nonetheless, the meaning of vacation to the parents of these children exudes notions of conflict and complication that locate mixed feelings. The study aimed at increasing the understanding on family tourists with children of special needs with different characteristics that may benefit the tourism providers and the autism therapists to collaborate on various innovative partnerships, producing platforms to facilitate a safe and enjoyable vacation experience to the targeted family as they travel together. Consequently, this effort can help dispel neglect in the social inclusion aspects regardless of the tourists’ physical or developmental conditions.